(3eG jYhd Ydjg aj GdeVGa hGdeVGa Edjgs - (3eMeO Cejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s
(3ChdgG (B:s
(3MeOkG ddg JYGdi faSg CLd eG jYhd Ydjg CeG HYO ajbhd eMeO GdCejf GdeMHi de CRd CLhH ai QjGV GdCOH hCJfGhd efg eG JJgGaJ ef HOGFYg NQO GdeYGfi hgh CLd cJGH hVYg GdKYGdHi CHh efUhQ s
(3BNQgG (B:s
(3hbGd GdTGYQ (B: (3ajhe YdjfG hjhe dfG hjhe fSGA hjhe fSQ hbGd BNQ hCjGe cCjGe GdTHGH bGd eDdag HQO Gddg eVLYg hCfRdg ai LhGQg Ydi GdQMH hGdSYI bO Je GdcJGH HYhf Gdedc GdhgGH s
(3HgG fXGe GdJYbjHIs
(3efbhdI Yf fSNI HNW GdeUfai aQZ efgG SfI (B1109 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B78s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GddZIs